2009
DOI: 10.4049/jimmunol.0803705
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of DNA Topoisomerase 1 Induces Systemic Sclerosis in the Mouse

Abstract: Systemic sclerosis (SSc) is a connective tissue disorder of great clinical heterogeneity. Its pathophysiology remains unclear. Our aim was to evaluate the relative roles of reactive oxygen species (ROS) and of the immune system using an original model of SSc. BALB/c and immunodeficient BALB/c SCID mice were injected s.c. with prooxidative agents (hydroxyl radicals, hypochlorous acid, peroxynitrites, superoxide anions), bleomycin, or PBS everyday for 6 wk. Skin and lung fibrosis were assessed by histological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
197
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(212 citation statements)
references
References 40 publications
8
197
0
7
Order By: Relevance
“…In these mice, skin fibrosis is induced by intradermal generation of HOCl that oxidizes skin proteins. This stress leads to the stimulation and proliferation of fibroblasts and to the overproduction of collagen and then to fibrosis [96]. The Keap1-Nrf2-ARE pathway likely contributes to this process.…”
Section: Possible Endogenous Trigger Of the Notch-nrf2 Axis: Rosmentioning
confidence: 99%
“…In these mice, skin fibrosis is induced by intradermal generation of HOCl that oxidizes skin proteins. This stress leads to the stimulation and proliferation of fibroblasts and to the overproduction of collagen and then to fibrosis [96]. The Keap1-Nrf2-ARE pathway likely contributes to this process.…”
Section: Possible Endogenous Trigger Of the Notch-nrf2 Axis: Rosmentioning
confidence: 99%
“…Furthermore, recent study demonstrated the direct role for ROS in the pathogenesis of SSc including autoantibody and collagen production in mouse model and human skin [20]. These results suggest that oxidative stress plays a role for development of SSc.…”
Section: Discussionmentioning
confidence: 69%
“…Servettaz et al developed the murine model of dermal sclerosis by repeated injection of ROS-inducing agents, including NaClO [23]. We have also reported that the ROS-producing agent Bleomycin induces systemic sclerosis [24], although Servettaz et al and our group have not examined the contribution of neutrophils to disease progression.…”
Section: Discussionmentioning
confidence: 99%